Violence against women in Chile: a criminogenic approach to guide public policy in the global south - Cadena-Urzúa, Pablo; Briz-Redón, Álvaro; Guardiola, Javier; Montes, Francisco (Frontiers in Political Science, 2025)
Violence against women is a pervasive social issue across the Global South, and Chile is no exception. This study aims to identify and analyze the criminogenic factors associated with violence against women in the cities of Concepción, Santiago, and Valparaíso during the period 2015–2019. A Poisson model with spatiotemporal covariates was employed to examine the influence of various factors, including previous incidents within the same area and neighboring areas, specific time slots, weekends, and demographic characteristics. The findings reveal a significant association between violence against women and these factors, underscoring the importance of temporal and spatial conditions in its occurrence. These results contribute to a deeper understanding of the phenomenon and emphasize the necessity of targeted public policies that integrate these variables for the effective prevention of violence against women in these regions. Additionally, this study highlights the need for further research that addresses the complexity of this form of violence from a comprehensive perspective, encompassing economic, social, and cultural factors. Overall, the research offers valuable tools for formulating intervention strategies aimed at reducing the prevalence of violence against women in Chile and improving the safety and well-being of affected individuals. These insights have broader implications for guiding future research and public policy in the Global South.